Overdose deaths and entrepreneurial activity - Albert Sumell (Economies, 2020)
Drug overdose deaths, primarily due to opioid addiction, have devastated communities in almost every area of the U.S. The economic impacts of the crisis include additional healthcare resources, unemployment, lost productivity, criminal justice costs, and other indirect impacts that have not yet been researched. This study aims to estimate one potential impact of opioid dependency in communities by estimating the relationship between drug overdose deaths and entrepreneurship. In particular, the empirical models measure how entrepreneurship, as measured by the percentage of self-employed workers, changes in relation to the number of overdose deaths in all U.S. counties, controlling for a number of socioeconomic characteristics. The results suggest that overdose deaths are associated with significant declines in self-employment rates. The coefficients on overdose death rates are generally larger in magnitude for rural counties than for larger metro counties.
Keywords: E61; L65; J21; 330; drugs; entrepreneurship determinants; labor; opioids; overdose; self-employment